Using Eco-indicator 99 and a two-stage nested analysis of variance test to evaluate building mitigation measures under hazard risks. Issue 5 (May 2016) - Ribakov, Y; Halperin, I; Pushkar, S
The study deals with life cycle assessment evaluation of mitigation measures for sustainable structural performance under earthquakes. A case study building using four different mitigation measures was evaluated. To analyze the mitigation measures, CO2 emissions, and environmental damages, six methodological options of Eco-indicator 99 addressing life cycle assessment uncertainties are employed. To compare the mitigation measures, a two-stage nested mixed balanced analysis of variance test is used. Three natural ground motion records were used for analysis. Percentages of the new environmental impact compared to the total building impact were obtained for each mitigation measure under the considered earthquakes. The results obtained on the Eco-indicator 99 damage evaluation level were not consistent with those on the CO2 emission. Along with the results of CO2 emission level, the Eco-indicator 99 damage level results should be disclosed by building designers and practitioners in the design process of mitigation measures.